1997
DOI: 10.1016/s0008-6363(97)00040-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical training on heart rate variability in diabetic patients with various degrees of cardiovascular autonomic neuropathy

Abstract: In diabetic patients with no or early CAN, regularly performed endurance training increased heart rate variability due to improved sympathetic and parasympathetic supply, whereas in subjects with definite/severe CAN no effect on heart rate variability could be demonstrated after this kind of training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
1
12

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 40 publications
3
72
1
12
Order By: Relevance
“…In contrast to other findings [52,62,63,64,65] this study did not show any covariation between age, physical activity, sex, or BMI and HRV parameters. Possible explanations could be, that the patients in our study consisted of a small and relatively homogenous group according to BMI and age.…”
Section: -H Time Domain Analysis Of Hrvcontrasting
confidence: 99%
“…In contrast to other findings [52,62,63,64,65] this study did not show any covariation between age, physical activity, sex, or BMI and HRV parameters. Possible explanations could be, that the patients in our study consisted of a small and relatively homogenous group according to BMI and age.…”
Section: -H Time Domain Analysis Of Hrvcontrasting
confidence: 99%
“…Although Meyer et al reported improvements in whole-body oxygen uptake capacity in heart failure patients following HIT exercise training (16), the present study indicates that the regular application of 4-8 exercise bouts of 30 s is insufficient to stress mitochondrial respiration in peripheral skeletal muscle (Table 2). However, this lack of response might also be attributed to our selected subject population, as it has been reported that genetic factors (67), older age (68) and diabetes-related co-morbidities attenuate the adaptive response in VO 2peak (14,61,64,69). Therefore, larger-scale studies are needed to gain more insight into the muscle fibre-type-specific adaptation following resistance, interval, endurance or combined types of exercise training in different T2D subpopulations.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that the adaptive response to exercise training is strongly determined by the presence of clinical signs of (autonomic) neuropathy and/or cardiorespiratory deconditioning (14). Therefore, the presence of co-morbidities should be taken into account when tailoring an exercise programme for longstanding, insulin-treated T2D patients.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of regular and sustained exercise regimen Olumide Olatubosun Rowaiye et al, Baroreceptor sensitivity and diabetes mellitus Not investigated in study -ALA -alpha-lipoic acid; BP -blood pressure; BPV -blood pressure variability; CAN -cardiovascular autonomic neuropathy; c-Fos-ir -c-Fos-immunoreactive; DM -diabetes mellitus; ECG -electrocardiography; HMG-CoA -3-hydroxy-3-methylglutaryl coenzyme A; ICV -intracerebroventricular; MABP -mean arterial blood pressure; MI -myocardial infarction; nNOS -neuronal nitric oxide synthase; NTS -nucleus tractussolitarius; RVLM -rostral ventrolateral medulla; STZ -streptozotocin in the management of the cardiovascular risks associated with DM cannot be overemphasized. Regular exercise has been shown to improve HRV parameters in patients with CAN (Table 4) with a deterioration of those parameters within weeks of complete exercise withdrawal [109]. [90] also appears to be useful in improving BRS in DM patients regardless of the duration (except of course in those with marked CAN).…”
Section: Clinical Perspective On Interventional Modalitiesmentioning
confidence: 99%